22q11.2 deletion syndrome and congenital heart disease. Issue 1 (12th February 2020) - Goldmuntz, Elizabeth
Abstract: The 22q11.2 deletion syndrome has an estimated prevalence of 1 in 4–6, 000 livebirths. The phenotype varies widely; the most common features include: facial dysmorphia, hypocalcemia, palate and speech disorders, feeding and gastrointestinal disorders, immunodeficiency, recurrent infections, neurodevelopmental and psychiatric disorders, and congenital heart disease. Approximately 60–80% of patients have a cardiac malformation most commonly including a subset of conotruncal defects (tetralogy of Fallot, truncus arteriosus, interrupted aortic arch type B), conoventricular and/or atrial septal defects, and aortic arch anomalies. Cardiac patients with a 22q11.2 deletion do not generally experience higher mortality upon surgical intervention but suffer more peri‐operative complications than their non‐syndromic counterparts. New guidelines suggest screening for a 22q11.2 deletion in the patient with tetralogy of Fallot, truncus arteriosus, interrupted aortic arch type B, conoventricular septal defects as well as those with an isolated aortic arch anomaly. Early identification of a 22q11.2 deletion in the neonate or infant when other syndromic features may not be apparent allows for timely parental screening for reproductive counseling and anticipatory evaluation of cardiac and noncardiac features. Screening the at‐risk child or adult allows for important age‐specific clinical, neurodevelopmental, psychiatric, and reproductive issues to be addressed.